Depuration kinetics of trinitrotoluene (TNT) and its metabolites in exposed blue mussels (Mytilus edulis L.) - Binder, Franziska Isabell; Schuster, Romina Marietta; Bünning, Lillian Tabea Hannah; Strehse, Jennifer Susanne; Brockmann, Mike; Herges, Rainer; Maser, Edmund; Brenner, Matthias (Frontiers in Marine Science, 2025)
Explosives released by dumped warfare material pose a threat to the marine environment and can enter the marine food web. 2,4,6-Trinitrotoluene (TNT) is one of the most used explosives in munitions and is, therefore, of special interest. To test the uptake, depuration, and potential biotransformation of TNT, common blue mussels (Mytilus edulis) from the German North Sea were exposed to different TNT concentrations in two laboratory experiments (first experiment, 48-h exposure to TNT concentrations of 0, 0.625, 1.25, and 2.5 mg/L; second experiment, 24-h exposure to 0 and 5 mg/L deuterated TNT) followed by recovery phases in clean artificial seawater (first experiment, 60-h recovery; second experiment, 12-h recovery). Water samples and mussel soft bodies were analyzed for TNT and its metabolites 2-amino-4,6-dinitrotoluene (2-ADNT), 4-amino-2,6-dinitrotoluene (4-ADNT), and 2,4-diamino-6-nitrotoluene (2,4-DANT) using Gas Chromatography – Tandem Mass Spectrometry (GC-MS/MS) techniques. The results showed a continuous uptake of dissolved TNT during exposure and a rapid depuration during the recovery phase, independent of the original TNT exposure concentrations. Furthermore, evidence for the biotransformation of TNT is shown by the presence of labelled ADNTs both in mussel soft bodies analyzed within the recovery phase and in water sampled during the recovery phase. Overall, 57% to 76% of the measured concentration was biotransformed within the first 4 h after the exposure.